Dimensional Stability of Wood Modified by Citric Acid - Samani, Ajmal; Hom, Sanjeet Kumar; Bhoru, Yasir Ullah; Ganguly, Sauradipta (Indian Forester, 2020)
Wood samples of Pinus roxburghii and Populus deltoides were chemically modified by using three different treatments and cured by convection 0heating at 140Â° C for 8 h. The dimensional stability of the modified wood was determined by evaluating anti-swelling efficiency using the water soak/oven dry method. Citric acid modification resulted in better dimensional stability compared to control samples in both the species. The current study indicates that treatment with Citric acid 13.8% and Sodium hypophosphate 13.0% resulted in optimal improvement in dimensional stability of wood.